The lack of digital equipment as the primary barrier to teleconsultation in a socially deprived French department during the COVID-19 epidemic period - Jeanne Goupil de Bouillé; Alexia Mubuanga; Claire Tantet; Soline de Monteynard; Lotfi Dahmane; Ségolène Brichler; Frédéric Méchaï; Hugues Cordel; Nicolas Vignier; Olivier Bouchaud (Digital Health)
Introduction The digital transition is spreading throughout the healthcare field but is also subject to a digital divide. This study aimed to determine the factors associated with patients’ inability to carry out teleconsultations during the COVID-19 epidemic in a French hospital located in a disadvantaged area close to Paris. Methodology This study is a secondary analysis of the SocialCov study, a published monocentric case-control study conducted on patients hospitalized for COVID-19 and control patients hospitalized for another reason. Data regarding teleconsultation, socio-demographic characteristics, and health literacy level were collected using a hetero-administered questionnaire. Factors associated with the inability to conduct a teleconsultation were identified using univariate and multivariate logistic regression. Results Among 240 patients,142 (59%) were male, and 105 (44%) were aged >65 years. Overall, 163 (68%) reported their inability to carry out a teleconsultation including 125 (52%) due to the absence of suitable digital equipment. In multivariate analysis, lack of adequate digital equipment was associated with the inability to carry out a teleconsultation (adjusted odds ratio [aOR] = 15.5; 95% CI [6.3, 38.3]). A trend was also observed with age >65 years (aOR = 2.1; 95% CI [0.9, 5.0], p  = 0.08) and the presence of a low health literacy (aOR = 2.4; 95% CI [0.9, 5.0], p  = 0.08). Conclusion In a French socially deprived area, access to technological devices is the primary barrier to conducting teleconsultations during the COVID-19 epidemic. To avoid exacerbating the digital divide, specific solutions must be proposed to reach digitally distant populations, addressing both material and digital literacy aspects.